2014
DOI: 10.3389/fnins.2014.00364
|View full text |Cite
|
Sign up to set email alerts
|

Functional and genetic analysis of choroid plexus development in zebrafish

Abstract: The choroid plexus, an epithelial-based structure localized in the brain ventricle, is the major component of the blood-cerebrospinal fluid barrier. The choroid plexus produces the cerebrospinal fluid and regulates the components of the cerebrospinal fluid. Abnormal choroid plexus function is associated with neurodegenerative diseases, tumor formation in the choroid plexus epithelium, and hydrocephaly. In this study, we used zebrafish (Danio rerio) as a model system to understand the genetic components of chor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 64 publications
(102 reference statements)
1
51
0
Order By: Relevance
“…This expression pattern was maintained into adulthood (data not shown). To examine mCherry expression in vasculature of circumventricular organs that lack BBB properties (Saunders et al, 2008), we crossed glut1b:mCherry to cp:EGFP, an enhancer trap line that expresses GFP in the choroid plexus (Henson et al, 2014), and injected albumin Alexa Fluor 647 conjugate to visualize the vasculature. We found that mCherry was not expressed in the vasculature of the choroid plexus (Figure 1G–J).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This expression pattern was maintained into adulthood (data not shown). To examine mCherry expression in vasculature of circumventricular organs that lack BBB properties (Saunders et al, 2008), we crossed glut1b:mCherry to cp:EGFP, an enhancer trap line that expresses GFP in the choroid plexus (Henson et al, 2014), and injected albumin Alexa Fluor 647 conjugate to visualize the vasculature. We found that mCherry was not expressed in the vasculature of the choroid plexus (Figure 1G–J).…”
Section: Resultsmentioning
confidence: 99%
“…Et(cp:EGFP) was previously generated in our lab (Henson et al, 2014). Embryos and larvae were maintained at 28.5°C in egg water (0.03% Instant Ocean in reverse osmosis water).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the model that systemic signals regulate ChP 129 , together with findings that CSF composition and mixing with the interstitial fluid maintain the health of the brain via convective flux more generally than previously believed 137139 (BOX 3), raise tantalizing hypotheses for the myriad ways by which CNS health can be regulated. Collectively, pairing actively evolving technologies with available models, including recently developed fluorescent ChP zebrafish lines 140 , should accelerate steps towards further elucidating the biology of the ChP–CSF system as well as advancing future therapies, including the transplantation of engineered ChP epithelial cells.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Similar to the ocular vasculature in mammalian embryos, zebrafish embryos possess choroidal and hyaloid networks that function similarly to their mammalian counterparts . In order to better understand how the fzd4 mutation affects retinal vascularization, and to determine the time point at which fzd4 vasculature formation deviates from its control counterpart, we followed the developmental progression of the retinal vasculature in control and fzd4 fish for the first 12 weeks of development (n = 10 fish/genotype/week).…”
Section: Resultsmentioning
confidence: 99%